The Russian invasion of Ukraine, fertilizer prices, and food security: Evidence from rice-producing economies in Asia - Ashok K. Mishra; Harold Glenn A. Valera; Takashi Yamano; Valerien O. Pede (Asian Development Bank (ADB), 2024)
This study assesses the impact of increased fertilizer prices under different scenarios on rice production, consumption, trade and prices. Using a global rice model based on a partial equilibrium framework, the simulation results show that a 30% to 100% increase in fertilizer prices would reduce rice yields by 0.45% to 1.33%, but increase world rice prices by 7% to 23% between 2022 and 2025. As the world market price for rice increases significantly, rice trade and rice consumption will decrease accordingly, estimated at 1.7% to 7.0% and 0.27% to 0.78%, respectively. The simulation results also show that retail prices for rice would increase significantly in all rice-consuming countries. The impact of higher fertilizer prices would vary widely in the major rice-producing countries.
Keywords: Q17; Q18; F51; 330; rice; world prices; Asia; rice trade; food security; partial equilibrium model